GAMIFICATION AND SOLO TAXONOMY: A STRATEGY TO PROMOTE ACTIVE ENGAGEMENT AND DISCIPLINE IN ENGLISH LANGUAGE LEARNING - Suryani, Nyayu Yayu; Syahbani, Muhammad Husni (University of Kuningan, 2023)
The motivation for this study arises from the potential of gamification, particularly the integration of game-based platforms like Kahoot!, to enhance active communicative language use within the classroom. The research aims to investigate the impact of implementing gamification based on SOLO taxonomy's relational level on the Kahoot! application on active participation, discipline, and learning outcomes in the context of English language learning. This study employs a descriptive research methodology, involving observations, interviews, and assessments, with a participant group comprising 35 nursing program students. Descriptive analysis reveals that gamification within the SOLO taxonomy framework positively influences students' active engagement and discipline, although there are fluctuations in their learning outcomes. Students express enthusiasm for utilizing the Kahoot! application for English learning, but they encounter occasional connectivity issues that hinder problem-solving activities. Consequently, the integration of technology is a promising approach for enhancing English language skills, with a reliable internet connection being a critical factor for success when using the Kahoot! platform.